2020
DOI: 10.3390/su12229450
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study for European Countries: Factors Affecting Economic Growth and Self-Employment by Gender

Abstract: In economic literature, the relationship between entrepreneurship and economic growth has been widely discussed for some time now. In addition to the different theoretical approaches, a considerable amount of empirical works in recent decades have sought to verify the direct link between both variables by analyzing datasets from several distinct geographic areas. On one hand, it highlights the absence of a common indicator to measure entrepreneurship in practice relating to a country’s economic growth; on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…In fact, Shane and Venkataraman [2] point out that analyzing the process of starting a new business should consider the individual and the opportunity. Regarding economic factors, the literature has extensively analyzed the positive effects of entrepreneurship on the economic growth of the countries [44]. Additionally, a favorable and stable economic system helps to create the conditions for a new business, facilitates the perception of opportunities and allows agents to operate with confidence [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, Shane and Venkataraman [2] point out that analyzing the process of starting a new business should consider the individual and the opportunity. Regarding economic factors, the literature has extensively analyzed the positive effects of entrepreneurship on the economic growth of the countries [44]. Additionally, a favorable and stable economic system helps to create the conditions for a new business, facilitates the perception of opportunities and allows agents to operate with confidence [8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the GEM database, in the past 20 years, less than 50 countries per year on average are covered. Brás and Soukiazis (2019) pointed out that the TEA focuses mostly on developed countries, which led other researchers, namely, Biltagy et al (2017), Aydoğan and Sevencan (2018), Sánchez (2018) and González-Sánchez et al (2020) to use the self-employment rate as an alternative proxy for entrepreneurship.…”
Section: Methodsmentioning
confidence: 99%
“…Although some empirical studies revealed a negative association between self-employment and income growth (Acs et al, 1994) (Barros & Pereira, 2008, others confirmed that selfemployment has positive impacts not only on income growth (Carpenter & Loveridge, 2017) (González-Sánchez et al, 2020 but also poverty reduction (Goetz et al, 2012), and regional development (Matejovsky et al, 2014). The factors that may cause uncorrelated motion between self-employment and income growth are, e.g., geographic location and education, race, age, and gender (Willis et al, 2020).…”
Section: An Association Between Women Self-employment and Economic Growthmentioning
confidence: 99%